Предмет: Математика,
автор: sashaminaeva0
как решить:
-5*(0,4х-0,6)=7*(0,4х-0,1)-1,1
Ответы
Автор ответа:
0
-5*(0,4х-0,6)=7*(0,4х-0,1)-1,1
-2х+3=2,8х-0,7-1,1
-2х-2,8х=-3-0,7-1,1
-4,8х=-4,8
х=-4,8:(-4,8)
х=1
Ответ:1
-2х+3=2,8х-0,7-1,1
-2х-2,8х=-3-0,7-1,1
-4,8х=-4,8
х=-4,8:(-4,8)
х=1
Ответ:1
Автор ответа:
0
спасибо большое✨
Автор ответа:
0
:)
Похожие вопросы
Предмет: Геометрия,
автор: Sbalka666
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: 4uvak25
Предмет: Алгебра,
автор: ласковая2
Предмет: История,
автор: Maria0001